2011
DOI: 10.1016/j.microrel.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Current transport mechanisms and trap state investigations in (Ni/Au)–AlN/GaN Schottky barrier diodes

Abstract: a b s t r a c tThe current transport mechanisms in (Ni/Au)-AlN/GaN Schottky barrier diodes (SBDs) were investigated by the use of current-voltage characteristics in the temperature range of 80-380 K. In order to determine the true current transport mechanisms for (Ni/Au)-AlN/GaN SBDs, by taking the J s(tunnel) , E 0 , and R s as adjustable fit parameters, the experimental J-V data were fitted to the analytical expressions given for the current transport mechanisms in a wide range of applied biases and at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…On the other hand, τ T-AlGaN for MIS-diodes A and B were between (2 -6 μs) and (5 -8 μs) respectively. These τ T-AlN and τ T-AlGaN are consistent with the τ T ranges generally reported for AlN related traps, 21 and AlGaN related bulk traps. 3 The trap state energy level (E T ) is proportional to the τ T , and therefore it can be deduced using the expression,…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, τ T-AlGaN for MIS-diodes A and B were between (2 -6 μs) and (5 -8 μs) respectively. These τ T-AlN and τ T-AlGaN are consistent with the τ T ranges generally reported for AlN related traps, 21 and AlGaN related bulk traps. 3 The trap state energy level (E T ) is proportional to the τ T , and therefore it can be deduced using the expression,…”
Section: Resultssupporting
confidence: 89%
“…The slope of this plot also provides a second determination of R s , which can be used to check the consistency of this approach. 20 The values of R s and n of samples MS and MPS obtained from dV=d lnðIÞvs. I plots according to Equation ( 3) are given in Table 1.…”
Section: The Electrical Properties Of the Diodes In Darkmentioning
confidence: 99%
“…In this case, while the donor type N SS is in effect near the conductance band, the acceptor type N SS is in effect near the valance band. 20 The electrical properties of the MPS diode under various illumination intensities Figure 6 shows the forward and reverse bias I-V characteristics at logarithmic scale of the Au/PVA(Nidoped)/n-Si MPS SD, measured in dark and at various illumination levels at room temperature. The forward current at high bias region increases with the increasing illumination intensity.…”
Section: The Electrical Properties Of the Diodes In Darkmentioning
confidence: 99%
“…The number of studies has been reported in the literature about the identification and elimination methods of the trap states in the GaN layer [21], AlGaN/GaN [11,12,16,17,19,20,23,24] AlInN/GaN [18,22], and AlN/GaN [25] heterostructures using frequency-voltage dependent capacitance and conductance measurement. Zhu et al [23] investigated the trap states in AlGaN/GaN Schottky-gate high-electron-mobility transistors (S-HEMTs) and Al 2 O 3 /AlGaN/GaN metal-oxide-semiconductor HEMTs (MOS-HEMTs).…”
Section: Introductionmentioning
confidence: 99%
“…Semra et al [25] reported a study on trap states in researching the gate-source contact on AlGaN/GaN HEMT by performing capacitance and conductance measurements at a temperature between 83 K and 370 K with the bias voltage maintained at 0 V. The interface trap state density and time constant were deduced using an analysis of the frequency dispersion in capacitance and conductance data. They established a traps state model with two levels of traps at the AlGaN/GaN interface and one level located in the barrier AlGaN surface with reported trap state values of 10 12 cm −2 eV −1 and a time constant varying between 1 μs and 3 ms.…”
Section: Introductionmentioning
confidence: 99%